Pelatihan Pengisian SPT PPh Orang Pribadi dan Badan serta Penggunaan E-Billing dan E-Filing - Meiriska Febrianti; Silvy Christina; Iman Akhadi; Muhamad Eddy Rosyadi; Tjhai Fung Jit; Eddy Joni; Ida Bagus Nyoman Sukadana (UKInstitute, 2023)
A self-assessment system is a tax collection system that allows taxpayers to calculate, pay and report the amount of tax that should be payable on their own based on tax laws and regulations. SPT is a tool used by taxpayers to account for the calculation of tax payable. An understanding of filling out the Annual SPT for individual and corporate taxpayers is needed, including the online system used for depositing and reporting taxes. Center for Research and Community Development (P3M) Trisakti School of Management also provides tax training through Community Service activities. The purpose of this community service activity is to provide an understanding of how to fill out the Annual SPT for individuals and entities and use e-billing and e-filing to make tax payments and reports. The method used in this training is through lectures, case studies, practice and question and answer. The results achieved in this training were that participants could understand the process of calculating and filling out individual and corporate annual tax returns and how to use e-billing and e-filing. The output target from this training is to provide an understanding of taxation to SMK students in terms of filling out Annual Individual and Corporate Income Tax Returns including procedures for payment and reporting taxes online. Abstrak: Self-assessment system merupakan sistem pemungutan pajak yang memberikan kepercayaan kepada Wajib Pajak untuk menghitung/memperhitungkan, membayar, dan melaporkan sendiri jumlah pajak yang seharusnya terutang berdasarkan peraturan perundang-undangan perpajakan. Surat Pemberitahuan (SPT) merupakan sarana yang digunakan oleh wajib pajak untuk mempertanggungjawabkan perhitungan pajak terutang. Pemahaman untuk pengisian SPT Tahunan baik bagi wajib pajak orang pribadi maupun badan sangat diperlukan, termasuk penggunaan online sistem yang digunakan untuk melakukan penyetoran dan pelaporan pajak. Pusat Penelitian dan Pengembangan Masyarakat (P3M) Trisakti School of Management turut berperan dalam memberikan pelatihan perpajakan melalui kegiatan Pengabdian Masyarakat. Tujuan kegiatan pengabdian masyarakat ini adalah untuk dapat memberikan pemahaman cara melakukan pengisian SPT Tahunan bagi orang pribadi dan badan serta penggunaan e-billing dan e-filing untuk melakukan penyetoran dan pelaporan pajak. Metode yang digunakan dalam pelatihan ini adalah melalui ceramah, studi kasus, praktek dan tanya jawab. Hasil yang dicapai dalam pelatihan ini adalah para peserta dapat memahami proses perhitungan dan pengisiaan SPT Tahunan orang pribadi dan badan serta cara penggunaan e-billing dan e-filing. Target luaran yang ingin dicapai dari pelatihan ini adalah dapat memberikan pemahaman perpajakan kepada siswa siswi SMK dalam hal pengisian SPT Tahunan PPh Orang Pribadi dan Badan termasuk tata cara penyetoran dan pelaporan pajak secara online